Actin maintains synaptic transmission by restraining vesicle release probability - Xin-Sheng Wu; Zhen Zhang; Yinghui Jin; Afreen Mushtaheed; Ling-Gang Wu (iScience)
Summary: Despite decades of pharmacological studies, how the ubiquitous cytoskeletal actin regulates synaptic transmission remains poorly understood. We addressed this issue with a tissue-specific knockout of actin β-isoform or γ-isoform, combined with recordings of postsynaptic EPSCs, presynaptic capacitance jumps or fluorescent synaptophysin-pHluorin changes, and electron microscopy in large calyx-type and small conventional hippocampal synapses. We found that actin restrains basal synaptic transmission during single action potential firings by lowering the readily releasable vesicle’s release probability. Such an inhibition of basal synaptic transmission is turned into facilitation during repetitive firings by slowing down depletion of the readily releasable vesicle pool and, thus, short-term synaptic depression, leading to more effective synaptic transmission for a longer time. These mechanisms, together with the previous finding that actin promotes vesicle replenishment to the readily releasable pool, may control synaptic transmission and short-term synaptic plasticity at many synapses, contributing to neurological disorders caused by actin cytoskeleton impairment.